Calcium Dynamics and Cardiac Arrhythmia. Issue 11 (1st December 2017) - Deo, Makarand; Weinberg, Seth H; Boyle, Patrick M
This Special Collection will gather all studies highlighting recent advances in theoretical and experimental studies of arrhythmia, with a specific focus on research seeking to elucidate links between calcium homeostasis in cardiac cells and organ-scale disruption of heart rhythm.